Changes in lung immune cell infiltrates after electric field treatment in mice - Sophia I. Eliseeva (Nature Portfolio, 2021)
Abstract Exogenous electric fields are currently used in human therapy in a number of contexts. Interestingly, electric fields have also been shown to alter migration and function of immune cells, suggesting the potential for electric field-based immune therapy. Little is known as to the effect of electric field treatment (EFT) on the lung. To determine if EFT associates with changes in lung immune cell infiltration, we used a mouse model with varying methods of EFT application and measured cells and soluble mediators using flow cytometry and cytokine/chemokine multiplex. EFT was associated with a transient increase in lung neutrophils and decrease in eosinophils in naïve mice within 2 h of treatment, accompanied by an increase in IL-6 levels. In order to test whether EFT could alter eosinophil/neutrophil recruitment in a relevant disease model, a mouse model of allergic airway inflammation was used. Four EFT doses in allergen-sensitized mice resulted in increased neutrophil and reduced eosinophil infiltrates following allergen challenge, suggesting a durable change in inflammation by EFT. Mice with allergic inflammation were analyzed by flexiVent for measures of lung function. EFT-treated mice had increased inspiratory capacity and other measures of lung function were not diminished. These data suggest EFT may be used to manipulate immune cell infiltration in the lung without affecting lung function.